Assessing potential surrogates of macroinvertebrate diversity in North-African Mediterranean aquatic ecosystems. (June 2019) - Slimani, Noura; Sánchez-Fernández, David; Guilbert, Eric; Boumaïza, Moncef; Guareschi, Simone; Thioulouse, Jean
Highlights: Macroinvertebrate taxa are assessed as surrogates of aquatic biodiversity in Africa. We found congruence among their patterns of species richness and composition. Higher-taxa (mainly genus) can be used to predict species diversity. We propose the use of Ephemeroptera and Coleoptera at genus level as surrogates. Abstract: The need to use surrogates of biodiversity is quite relevant in threatened habitats harboring high values of biodiversity, such as the Mediterranean aquatic ecosystems. In this study, we assess the performance of eight macroinvertebrate groups (Coleoptera, Heteroptera, Odonata, Trichoptera, Plecoptera, Ephemeroptera, Crustacea, and Mollusca) as surrogates of the whole aquatic macroinvertebrate assemblage in 49 localities from Northern Africa (Tunisia). Specifically, we aimed to test i) the congruence of the patterns of species richness and composition among these eight groups (at species level) in order to propose which groups could be accurate as indicators of diversity of the whole community, and ii) if higher-taxon levels (genera or families) are suitable for predicting overall species richness and composition in these ecosystems. In total, we found 72 families, 157 genera and 280 species. Our results show a high congruence between the patterns of species richness and composition of Ephemeroptera, Coleoptera (even at higher taxonomic levels, especially genus) and the whole community. Thus, we recommend the use of these two groups as surrogates of macroinvertebrate diversity in inland aquatic ecosystem in the study area. They can be used for both i) the rapid and inexpensive monitoring of biodiversity in aquatic ecosystems and ii) conservational studies in order to identify areas with the highest values of freshwater biodiversity in Mediterranean areas. Finally, high values of congruence among taxonomic levels were found suggesting that, in general, higher taxa can be used as biodiversity surrogates for cost-effective practical survey in Mediterranean aquatic ecosystems from Northern Africa.